Investigation of Sclerocarya birrea seed oil extracted as a bioenergy resource for compression ignition engines - Ejilah, Robinson Ichakpa; Lukman, Abdulkadir; Bello, Adisa Ademola (International Journal of Agricultural and Biological Engineering, 2012)
Sclerocarya birrea (Marula) seed oil was extracted and characterized for its physico-chemical properties and fatty acid compositions, respectively, by using standardized laboratory methods of the Association of Official and Analytical Chemist (AOAC). The fuel and lubrication properties of marula oil were also determined by using the ASTM methods, and the oil was evaluated in terms of its antiwear, viscometrics, volatility, stability, environmental compatibility properties and energy content. It was found that the high percentage of mono-unsaturated oleic acid (73.6%) provided the oiliness that makes marula oil a natural alternative to genetically modify high oleic acid sunflower oil used in biodiesel production. The aggregate properties of seed oiliness as exemplified by the high oleic acid content, high saponification value (178.6 mg/KOH) and viscosity (41 mm2/s) makes marula oil to be prospective based oil for engine crank case biolubricants with antiwear and friction reduction properties. However, the higher oil viscosity exhibited by marula seed oil in comparison to diesel could pose some durability problems to compression ignition engines, when used directly as fuel. Nonetheless, the reduction of oil viscosity would be required by heating, blending with diesel fuel, or by transesterification to forestall the risk of engine failure resulting from the use of unmodified marula oil. The flash point of marula oil (235